2023
DOI: 10.1001/jamanetworkopen.2023.2931
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Emergency Department Use Before Pregnancy and Infant Emergency Department Use After Birth

Abstract: ImportanceMaternal emergency department (ED) use before or during pregnancy is associated with worse obstetrical outcomes, for reasons including preexisting medical conditions and challenges in accessing health care. It is not known whether maternal prepregnancy ED use is associated with higher use of the ED by their infant.ObjectiveTo study the association between maternal prepregnancy ED use and risk of infant ED use in the first year of life.Design, Setting, and ParticipantsThis population-based cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Possibly, similar reasons are leading to our observations in IBD, particularly as healthcare utilization in the remote immigrant group was similar to the non-immigrant group suggesting acculturation (35). Nonetheless, observed disparities in healthcare utilization in immigrant groups during pregnancy remains alarming because it may suggest poor ambulatory gastroenterology and prenatal care access (15,36), which in turn may result in poor outcomes such as preterm birth and neonatal death (10,16–18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly, similar reasons are leading to our observations in IBD, particularly as healthcare utilization in the remote immigrant group was similar to the non-immigrant group suggesting acculturation (35). Nonetheless, observed disparities in healthcare utilization in immigrant groups during pregnancy remains alarming because it may suggest poor ambulatory gastroenterology and prenatal care access (15,36), which in turn may result in poor outcomes such as preterm birth and neonatal death (10,16–18).…”
Section: Discussionmentioning
confidence: 99%
“…These issues may be further amplified during pregnancy because of heightened provider and patient concerns (9,10). Previous studies have demonstrated that, compared with non-immigrant women, immigrant women are less likely to receive adequate prenatal care, which in turn increases the risk of adverse pregnancy outcomes, such as preterm delivery and low birth weight (LBW) (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, in terms of predisposing factors, we found that there was an inverse association between paediatric patients brought in by their fathers and NUPs. On the one hand, this may be due to the fact that mothers tend to be the PC givers and therefore attend PEDs more often than fathers (Varner et al., 2023). On the other hand, the higher levels of psychological distress reported by mothers compared to fathers during visits to the PED may provide an alternative explanation (Montoro‐Pérez et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that suboptimal health outcomes during this life-stage stem from inequitable access to and subsequent engagement in prenatal care services [ 8 , 9 ]. Studies have identified that inadequate prenatal care can result in a higher risk of complications during and after pregnancy for the birthing individual and infant [ 10 16 ]. Our review focuses on the prenatal period as adequacy of care during this time can influence subsequent physiological and psychological experiences during birth and the postpartum period [ 10 17 ].…”
Section: Introductionmentioning
confidence: 99%